Evaluation of 300 WP Solar Photovoltaic Panel Performance for Electric Vehicle Charging Station - Dionova, Brainvendra Widi (Politeknik Negeri Semarang, 2023)
Conventional transportation methods result in the release of harmful greenhouse gases into the environment. Electric vehicles offer an alternative to mitigate this environmental harm. Electric Vehicle Charging Stations (EVCS) are crucial infrastructure components for supporting electric vehicles. Photovoltaics represents a facet that can be integrated into EVCS to improve eco-friendly power generation. Various factors, including temperature, humidity, and light intensity, influence electricity generation in photovoltaic (PV) systems. This research examines the consequences of temperature, humidity, and light intensity fluctuations within EVCS. During the system integration testing conducted between 09:00 and 16:00, it was noted that there is an inverse relationship between air humidity and temperature; when air humidity increases, temperature decreases, and vice versa. The solar panel exhibits its highest sunlight intensity reception between 09:30 and 15:30. The peak power output from the solar panel was registered at 13:00, with an air temperature of 40.40 °C, air humidity at 35%, and light intensity at 54.61 Cd, resulting in a solar panel power output of 146.1 Watts. Conversely, the lowest power output from the solar panel was observed at 16:00, with an air temperature of 31.80 °C, air humidity at 54%, and light intensity at 39.39 Cd, leading to a solar panel power output of 107.36 Watts. Anticipated findings from these analyses are expected to contribute to future technological advancements, enabling the creation of competitive products in the market.